If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3-1)(1+x)(-2)=2x
We move all terms to the left:
(3-1)(1+x)(-2)-(2x)=0
We add all the numbers together, and all the variables
2(x+1)(-2)-2x=0
We add all the numbers together, and all the variables
-2x+2(x+1)(-2)=0
We multiply parentheses ..
-2x+2(-2x-2)=0
We multiply parentheses
-2x-4x-4=0
We add all the numbers together, and all the variables
-6x-4=0
We move all terms containing x to the left, all other terms to the right
-6x=4
x=4/-6
x=-2/3
| 1x+1=5x+5 | | 7c−4c+c−c=12 | | | | -4(u+3)=-3(4u-1)+2u | | c2+11c+30=0 | | 1x-1=2x+1 | | 16^(3x)=8^x+6) | | 11/7b=4 | | y^2+11y-196=0 | | 7x+44=9(x+4) | | 7(w+3)=2w+26 | | 3x+1.4=2.9 | | 0=0.03x(x-100) | | 2w-2=4(w+4) | | 1x-2=3x+12 | | 25/12=x/12 | | 2x-2=1x+7 | | 26=7(v+6)-5v | | 15+x/3=12 | | -34=6(y-8)-4y | | 1x+18=5x+6 | | | | 4=3w+4(w+8) | | 216+43.2=x | | 5x+19=1x+7 | | 4/13=2b/13=6b/26 | | -11+x/11=-13 | | y/4=7/17 | | 1x+9=2x+4 | | 2x+3x+7+6x-3=180 | | 1x+9=2x=4 | | (e/3)=7 |